Utilizing Earth and Space Sciences In The Light Of the Next Generation Science Standards (NGSS) for Improving Scientific and Engineering Practices among preparatory stage pupils - Amany Elgendy; Rafeek Elmeanawy (Port Said Journal of Educational Research, 2023)
The current research aimed to use earth and space sciences in light of the next-generation science standards (NGSS) to improve scientific and engineering practices among middle school students. The research followed the quasi-experimental design, a pre-post one-group design for experimenting with the developed Earth-Universe Unit. The participants consisted of 30 female students. The materials for the research tools were a student’s book, a teacher’s guide, and a learner’s activity booklet. The tool of the study was a scientific and engineering practices test. The results revealed that there is a statistically significant difference between the mean scores of the participants in the pre and post-administration of the scientific and engineering practices test at the level (0.05) in favor of the post-application. This means the effectiveness of the developed curriculum (Unit of the Earth and the Universe) in the light of NGSS in science for the first grade of middle school. The research also recommended the necessity of paying attention to the Next Generation Science Standards in developing science curricula in the preparatory stage, especially in the field of the universe and earth sciences.